Pengaruh Motivasi Terhadap Produktivitas Kerja Pegawai Pemerintah Dengan Perjanjian Kerja (PPPK) di Kantor Pertanahan Kota Denpasar Tahun 2016 - Rezadana, I Gede Abicatra; Erviantono, Tedi; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2016)
ABSTRACT Giving motivation to employees has an important role to increase their productivity. One of the examples can be found on Government Employees with Labor Agreement (PPPK)at Land Office in Denpasar. The aim of this study was to find out the impacts of motivation towards working productivity. The method used in this study was quantitative method. The primary data was obtained by 55 questionnaires. The analysis showed that motivation had a positive and significant impact towards working productivity. Furthermore, the result of determination of R2 (R-square) was 58.0% and the remaining 42.0 % was influenced by other factors. Based on a simple linear regression analysis, it was seen that if the motivation was constant then productivity amounted to 5.728. However, if the motivation was increased 1 %, then the productivity would increase by 0.921. Moreover, based on significance test, it was obtained that tvalue (8,559) wasgreater than ttable (1,673). Â  Keyword: Motivation, Working Productivity, PPPK